EVALUATION THE EFFICIENCY OF SUBSTATE AND CASING IN YIELD CHARACTERISTICS AND QUALITIES OF FUNGI Pleurotus eryngii - & et al., Abdulrazzaq (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
Evaluation the efficiency different agro-waste sawdust (SD) , wheat straw (WS) and palm waste (PW) substrate on morphological and productivity of the P. eryngii showed that the shortest period for the full growth was on PWs which reached 53.3 days , the shortest period of pinhead formation was 8.7days on SD , the fungus gave the maximum yield and biological efficiency on WS which reached 138.3 gm/bag and 37.7 % . the shortest period of full growth of P. eryngii in SD supplemented with alfalfa was 20.6 days , the shortest period of pinhead formation was 12days on treatments WS enriched with wheat bran , WS amended with sugarcane and SD amended with wheat bran The fungus gave the highest yield in WS enriched with wheat bran which246.3 gm/bag in the same substrate with 74.5 % biological efficiency. The general mean growth for P. eryngii was 1cm / day on different examined soil which achieved the highest general mean growth 3 cm after 3 days of inoculation on Peatmoss + clay soil (1:1, the highest yield 790 gm / container in WS enriched with wheat bran with 119% biological efficiency by peatmoss alone.